(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Morphological processes alter a word’s root or base, modifying its meaning. The suppletive process, originating from the Latin verb "supleõ," can only occur in closed groups. Regular and irregular variants are necessary to explain suppletion. Old English and Old High German share similarities in suppletive verbs. Sufixative verbs derive their grammatical structures from various roots, such as the Old English verb "beon" and Old High German verb "wesan." These verbs have parallel forms and different origins.